HOVHANNES TUMANYAN BY THE EVALUATION OF RUSSIAN TRANSLATORS (30-60S OF XX CENTURY) - JANPOLADYAN, MAGDA (Bulletin of Yerevan University H: Russian Philology, 2019)
The article analyzes the opinions of russian translators Vera Zvyagintseva, Samuil Marshak and Sergey Shervinsky on the poetry of Hovhannes Tumanyan. The research material shows that the authors have mainly expressed very interesting, important ahd specific thoughts about the essence and peculiarities of Tumanjans work, emphasizing the world value of the Armenian poet. There are persuasive theses ahd some inaccuracies (in S. Shervinskys article) that are being challenged.
Keywords: Tumanyan, opinions of russian translators, Zvyagintseva, Marshak, Shervinsky, valuable observations, controversial thoughts, highlighting the world value of the Armenian poet